PENINGKATAN PENGETAHUAN PENGGUNAAN ANTIBIOTIK YANG BIJAK MELAUI ISTILAH KOMUNIKATIS DAGUSIBU DI DESA - Mahardika, Muladi Putra; Pratiwi, Rosaria Ika (Universitas Muhammadiyah Mataram, 2024)
Abstrak: Masalah resistensi antibiotik merupakan masalah global yang disebabkan oleh tidak tepatan penggunaan antibiotik dan kurangnya pengetahuan pada masyarakat. Permasalahan tersebut dapat diatasi melalui pemberdayaan masyarakat dengan edukasi tentang Antibiotik dan DAGUSIBU melalui media leaflet. Istilah DAGUSIBU merupakan salah satu upaya edukasi dan pembelajaran kepada masyarakat untuk meningkatkan pemahaman, kepedulian dan kesadaran masyarakat terkait penggunaan obat secara tepat dan benar. Tujuan kegiatan ini memberikan informasi dan meningkatkan pengetahuan kepada masyarakat tentang bahaya penggunaan antibotik yang tidak tepat. Kegiatan pengabdian kepada masyarakat ini dilakukan dalam bentuk penyuluhan dan pemutaran video DAGUSIBU penggunaan antibiotik. Pengukuran keberhasilan kegiatan dilakukan dengan memberikan 20 butir pertanyaan tentang antibiotic dalam bentuk pretest dan postets kepada ibu-ibu PKK dan Kader Posyandu. Perhitungan persentasi total masyarakat yang dapat menjawab soal dengan tepat. Dari hasil pengolahan data, diketahui bahwa terjadi peningkatan pemahaman dan pengetahuan masyarakat terkait resistensi antibiotik setelah diberikan penyuluhan sebesar 36,67%.Abstract: The problem of antibiotic resistance is a global problem caused by inappropriate use of antibiotics and lack of knowledge in the community. These problems can be overcome through community empowerment with education about antibiotics and DAGUSIBU. The purpose of this activity is to provide information and increase public knowledge about the dangers of improper use of antibiotics. Community service activities are conducted in the form of counseling and video playback DAGUSIBU antibiotic use. Measurement of the success of the activity was carried out by providing 20 questions about antibiotics in the form of pretests and postets to PKK mothers and Posyandu cadres. Calculation of the total percentage of people who can answer the question correctly. From the results of data processing, it is known that there is an increase in public understanding and knowledge related to antibiotic resistance after counseling is given by 36.67%.The problem of antibiotic resistance is a global problem caused by improper use of antibiotics and lack of knowledge in the community. These problems can be overcome through community empowerment with education about antibiotics and DAGUSIBU through leaflet media. The term DAGUSIBU is one of the efforts of education and learning to the community to increase understanding, concern and public awareness related to the use of drugs appropriately and correctly. The purpose of this activity is to provide information to the public about the dangers of improper use of antibiotics. Community service activities are conducted in the form of counseling and video playback DAGUSIBU antibiotic use. Measurement of the success of the activity was carried out by providing pretests and postets to PKK mothers and Posyandu cadres. Calculation of the total percentage of people who can answer the question correctly. From the results of data processing, it is known that there is an increase in public understanding and knowledge related to antibiotic resistance after being given a 36.67% ignition.